Cooperative control of the DC-link voltage in VSC-MTDC grid via virtual synchronous generators - Han, Huachun; Li, Qun; Li, Qiang (Frontiers in Energy Research, 2024)
Virtual Synchronous Generators (VSGs) are utilized in Voltage Source Converter-based Multi-Terminal High-Voltage Direct Current (VSC-MTDC) systems to improve power system stability. However, the MTDC framework inherently segments the grid into areas of reduced inertia, which can create instability during load switching due to continuous power fluctuations at VSC stations. A disruption in the power balance, caused by untimely adjustments of the VSG's power setpoint, may provoke oscillations in voltage and frequency, compromising the system's stability. Simultaneously, in the process of using wind farms for frequency regulation, wind turbine units may cause a secondary frequency drop (SFD) in the system during the speed recovery. To mitigate this issue, this study introduces a cooperative control approach for the DC voltage of the VSG via using the consensus algorithm and Model Predictive Control (MPC) to obtain incremental power for VSG, and providing interactive power commands for the grid side and the wind farm side. The consensus algorithm facilitates the convergence of system adjustments, fostering coherence in the cooperative control approach. Concurrently, the MPC algorithm enables real-time tracking of DC-side voltage changes within the system. The increase in supplemental power not only fully utilizes the energy stored in the DC-side capacitors for power balance regulation but also infuses additional inertial power into the system. The proposed cooperative control significantly enhances DC voltage regulation performance, reduces the extent of frequency drops, and effectively mitigates secondary frequency drop issues. The effectiveness of the Consensus MPC-VSG method is confirmed through electromagnetic transient simulations. Findings suggest that employing this method can optimize the dynamic performance of VSC-MTDC systems, promoting stability in DC voltage and frequency.